Investigating learning difficulties in economics English medium classes among Malay students / Roslilee Ab. Halim and Norliwa Ab. Halim - Ab. Halim, Roslilee; Ab. Halim, Norliwa (Universiti Teknologi MARA Cawangan Pahang, 2013)
English language is spoken globally where many people in the world purposely learn it as a second language. In order to prepare students to venture into this global world and be part of the growing society, many universities are using English as the medium of instruction in lectures or tutorials. For most Malay students whose mother tongue is not English, the level of English proficiency might influence their capability in comprehending the courses taught. A very minimal ability in English would lead to learning difficulties. This will definitely disturb the learning process. As such, the main objective of the paper is to investigate the learning difficulties faced by the Malay students in comprehending the subject with English as the medium of instruction. 100 questionnaires were distributed among Malay students who enrolled for Economics courses. The selection of sample was based on simple random technique. The findings showed that the overall degree of students' comprehension in their Economics English-medium classes is at the average level and that the comprehension level will improve if the lecturers reexplain in their mother tongue language which is Malay (M=4.14). About half of the respondents were found to respond that the difficulties in understanding Economics were due to either solely to the difficulty they had with English language or at least part of the difficulty was due to English.